Pendampingan Pembuatan Sistem Keamanan Jaringan Menggunakan Firewall Open Source Di SMK Garuda Nusantara - Siswandi, Arif; Soejarminto, Yos; Rilvani, Elkin; Muktiali, Saiful (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
The rapid development of information and network technology requires vocational schools to implement reliable network security systems to protect digital infrastructure and data. SMK Garuda Nusantara has adequate network facilities; however, network security implementation has not been optimally configured. This community service program aims to provide assistance in developing and implementing an open-source firewall-based network security system. The implementation method includes preparation, socialization, theoretical training, firewall configuration practice, mentoring, and evaluation. Open-source firewall solutions are utilized as cost-effective and educational tools for network security learning. The results indicate improved participants’ understanding and skills in network security concepts, traffic management, and access control using firewalls. This program supports project-based learning, enhances cybersecurity awareness, and strengthens collaboration between higher education institutions and vocational schools. Keywords: Network Security, Open Source Firewall, Community Service, Vocational Education